Religious Diversity and Coexistence in Jhumpa Lahiri’s Short Stories: “The Blessed House” and “When Mr. Pirzada Came to Dine" - Jassim, Isra Hasan (Al-Adab Journal, 2019)
Religion is one of the themes tackled in literature providing a source of conflict, especially the diversity of religions in the same country. Various religions are found in the same country leading to dispute and argument. Such arguments are usually heightened when individuals emigrate and settle in a country where the dominant religion is unlike theirs. Consequently, they have to achieve a compromise by negotiating the cultural and religious differences.Many of the immigrants in the united States of America descend from Asia. They are Hindu, Muslims, Budist,etc. Those immigrants faced a difficulty in accepting the American norms of life. They also had problems in accepting other religions. Jhumpa Lahiri’s Interpreter of Maladies is a collection of short stories that are set in the United States of America and India. Most of the characters are Indian immigrants who are trying to reconcile the cultural and religious differences in their new life in the States.The aim of this study is to investigate how various religions can coexist at the same time, in the same place. This coexistence is exemplified in the short story entitled “ The Blessed House.” The study also explores the reconciliation of different religions in a foreign country. In the short story entitled “when Mr. Pirzada Came to Dine,” Mr. Pirzada, a Pakistani man visits an Indian family in the United States of America and develops a truthful friendship with their daughter in spite of the differences in their age and religion